Restrictercise! Preferences Regarding Digital Home Training Programs During Confinements Associated with the Covid-19 Pandemic - Sanchez-Ramirez, C (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Confinement measures during the COVID-19 pandemic have caused substantial reductions in global physical activity (PA) levels. In view of the manifold health benefits of PA, the development of interventions counteracting this trend is paramount. Our survey with 15,261 participants (38 ± 15 years, 58.5% females) examined preferences towards digital home exercise programs in 14 countries affected by COVID-19. More than two-thirds of the sample (68.4%, n = 10,433) indicated being interested in home exercise, and most participants were willing to work out at least three times per week (89.3%, n = 9328). Binary logistic regression revealed that female sex, working part-time, younger age, and being registered in a gym were associated with willingness to exercise. Flexibility (71.1%, n = 7377), resistance (68.6%, n = 7116), and endurance training (62.4%, n = 6478) were the most preferred types of exercise. Our results may guide health providers in developing individually tailored PA interventions during the current and future pandemics. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.